Timing of Type I Open Distal Radius Fracture Fixation Does Not Affect Early Complication Rates - Eric R. Taleghani, MD; James Rex, MD; Samuel Gerak, BA; John Velasquez, MS; Kathryn Rost, BS; Sonu A. Jain, MD, FACS (Journal of Hand Surgery Global Online)
Purpose: There is limited published evidence regarding the optimal management of type I open fractures of the distal radius. The purpose of this study was to compare short-term complication rates among open fractures of the distal radius, with attention to the timing of management of type I fractures. Our hypothesis was that there would not be a temporal association between treatment and infection for type I open distal radius fractures (DRFs). Methods: A retrospective review of all open DRFs at a single level-1 trauma center over a 10-year period was performed. Patients were grouped based on Gustilo Anderson open fracture classification. The primary outcome measures were superficial and deep infection rates in all patients with a minimum of 6-month follow-up. A subgroup analysis was performed for Gustilo Anderson type I injuries with a 3-month follow-up based on time to surgery. Results: Seventy-one patients with open DRFs were included for analysis with an average follow-up of 16.7 months. There was a higher rate of deep infection (30%) and average number of revision surgeries (3.0) in the type III cohort compared with both type II (4% and 0.6) and type I (0% and 0.39) cohorts. A subgroup analysis of 63 type I fractures with a minimum of 3-month follow-up revealed zero infections, with no difference in other complications or number of revision surgeries among patients definitively managed within 24 hours, 24–72 hours, and greater than 72 hours. Two patients were managed nonoperatively, without complication. Conclusions: Type I open DRFs differ from higher grade DRFs with regard to demographics and injury characteristics, along with infection, complication, and reoperation rates. With no infections in the type I DRF cohort and no difference in complication rates based on time to debridement, our data suggest that it is safe to manage type I open DRFs similarly to closed injuries regarding surgical timing. Type of study/level of evidence: Therapeutic III.